Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.48550/arxiv.2005.10500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On memfractance of plants and fungi

Abstract: The key feature of a memristor is that the resistance is a function of its previous resistance, thereby the behaviour of the device is influenced by changing the way in which potential is applied across it. Ultimately, information can be encoded on memristors, which can then be used to implement a number of circuit topologies.Biological substrates have already been shown to exhibit some memristive properties.It is, therefore, logical that all biological media will follow this trend to some degree. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This is consistent with the intricate biomolecular roots of the dynamic memory that emerges from the layered proteinoid microsphere structures and changes in their shape during electrical testing. The displayed coefficient mappings offer a conceptual visualization of the complex inherent memory qualities of proteinoids using the mathematical framework of the generalized memfractance model . Quantitatively establishing a direct relationship between certain molecular pathways and recorded electrical memory signatures is a task that still has to be addressed in future research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the intricate biomolecular roots of the dynamic memory that emerges from the layered proteinoid microsphere structures and changes in their shape during electrical testing. The displayed coefficient mappings offer a conceptual visualization of the complex inherent memory qualities of proteinoids using the mathematical framework of the generalized memfractance model . Quantitatively establishing a direct relationship between certain molecular pathways and recorded electrical memory signatures is a task that still has to be addressed in future research.…”
Section: Resultsmentioning
confidence: 99%
“…The displayed coefficient mappings offer a conceptual visualization of the complex inherent memory qualities of proteinoids using the mathematical framework of the generalized memfractance model. 32 Quantitatively establishing a direct relationship between certain molecular pathways and recorded electrical memory signatures is a task that still has to be addressed in future research.…”
Section: Resultsmentioning
confidence: 99%
“…The application domain of the fungal electronic oscillators could be the field of unconventional computing [19], especially in the framework of organic electronics, living sensor and living computing wetware. Feasibility studies with plants [20,21], slime mould [22,23,24,25] and fungi [26,27] have shown that it is possible to develop electrical analog computing circuits either based or with these living creatures. Biological molecules such as suine microtubules have been shown to enable very fast oscillations, in the tents of MHz range [28].…”
Section: Introductionmentioning
confidence: 99%

On resistive spiking of fungi

Adamatzky,
Chiolerio,
Sirakoulis
2020
Preprint
Self Cite